Testing the effectiveness of alternatives to paraquat for the preparation of tracer belts in plantations, on farms and in the ecotourism industry in Swaziland - Reinhardt, Carl Frederick (Charlie) (2026)
Dissertation (MSc (Forest Management and the Environment))--University of Pretoria, 2018.